E-cadherin inhibits the proliferation and migration of human colorectal cancer cells through Hippo signaling pathway - Zhijing Wang; Xiaohua Qin; Shanshan Liu; Yilei Wen; Bikan Lan; Hantao Liao; Haixian Wei (European Journal of Histochemistry)
E-cadherin (E-cad) is a crucial regulatory factor in rescue Epithelial-mesenchymal transition and is involved in the occurrence of various malignant tumor. However, the mechanisms by which E-cadherin regulates tumor metastasis in CRC remain unclear. We established sh-E-cad (silenced by short hairpin RNA) and rescue-E-cad (overexpressed by E-cad plasmid transfection) CRC cell lines to investigate the role of E-cad in CRC in vitro. Immunohistochemistry, clonogenic assays, scratch wound healing assays, CCK-8 assays, flow cytometry, Transwell assay, real time-PCR and Western blot were employed to investigate the underlying mechanisms by which E-cad involve the progression of CRC. In CRC tissues, E-cad expression was significantly reduced, while YAP expression was markedly elevated. Silencing E-cad induced a significant increase of clonogenic ability in CRC cells, which was reduced upon rescue of E-cad expression. Transwell assays indicate that low expression of E-cad enhances the cell migration, a finding corroborated by scratch wound healing experiments. CCK-8 results demonstrate that silencing E-cad promotes the proliferation of CRC cells. Importantly, we found that E-cad influences apoptosis rather than the cell cycle. Analysis of Hippo signaling pathway-related factors revealed that silencing E-cad resulted in significantly decreased expression of MST1/2 and LATS1/2, as well as reduced phosphorylation levels of YAP, while YAP expression was significantly increased. Additionally, immunofluorescence confirmed the nuclear translocation of YAP. Our study indicates that E-cad regulates the malignant progression of CRC via the Hippo signaling pathway, offering a potential new strategy for CRC treatment.